Linking with Farmers : Networking for Low-External-Input and Sustainable Agriculture/ (Acc: 1101) networking for low-external-input and sustainable agriculture - Alders, Carine; Haverkort, Bertus; Veldhuizen, Laurens van.; International Institute of Rural Reconstruction; Informationcentre for Low External Input Agriculture; World Neighbors (Organization) (London, U.K. : Intermediate Technology Publications, 1993)
Contributed articles presented at an International Workshop on Networking for Low-external-input and Sustainable Agriculture in Silang, Philippines, in March 1992, organized by International Institute of Rural Reconstruction, World Neighbors and ILEIA.
Keywords: Networking for low External input and sustainable agriculture